Analisis Sosiolinguistik Variasi Pelafalan Bahasa Tidak Baku pada Siswa Sekolah Dasar dalam Pembelajaran Bahasa Indonesia - Witri Nisa Aulia; Adrias Adrias (Study program PGSD FKIP Universitas Bung Hatta, 2026)
This study was conducted based on the use of non-standard language among elementary school students, especially in pronunciation variations during communication and learning activities. The purpose of this study was to analyze the forms of non-standard pronunciation variations, the sociolinguistic factors influencing them, and their implications for Indonesian language learning in elementary schools. This study used a qualitative approach with a literature review method by examining ten journals related to the research topic. The results showed that the pronunciation variations included sound changes, sound omission, the use of non-standard vocabulary, and the use of informal language in formal situations. Social factors such as regional languages, peer interaction, and social media were found to influence students’ language use. Therefore, Indonesian language learning should encourage the use of standard language through reading, writing, and speaking activities to support students’ language development. Keywords: sociolinguistics; non-standard language; pronunciation variation; elementary school.